Pengaruh Konsentrasi Dan Lama Perendaman Asam Sulfat Terhadap Perkecambahan Biji Aren ( Arenga pinnata Merr. ) - SUFYAN ATSAURI TANJUNG; Ratna Rosanty Lahay; Mariati Mariati (Jurnal Agroekoteknologi, 2017)
ABSTRACT The influence of concentration and soaking time of sulfate acid to germination of sugar palm (Arenga pinnata Merr.) seeds. The research was conducted in Laboratory of Seed Technology, Agricultural Faculty, Univesity of Sumatera Utara, Medan, about 25 meters above the sea level started from November 2015 until Januari 2016using Randomized Block Design with two factors, i.e. concentration of sulfate acid with 4 levels : 0 %, 25 %, 50 %, 75 % andsoaking time with 4 levels : 5 minute, 10 minute, 15 minutes and 20 minute. The parameters observed were percentation of germination, germination rate, vigor index, axis embrio+radicule lenght, seedling fresh weight and dry weight. The results showed  that the interaction  between concentration and soaking time of sulfate acid significantly affected to all parameters observed except germination rate parameter. The combination seeds soaked in 75 % sulfate acidfor ten minutes produce the highest percentation of germination, vigor indeks, axis embrio+ radicule length, i.e. 100%, 0.31, 10.42 cm respectively. Key words : soaking time, sugar palm seeds, sulfate acid concentration